2007
DOI: 10.1103/physrevb.75.024108
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability and shear softening inCaSiO3perovskite at high pressure

Abstract: We predict the phase diagram of CaSiO 3 perovskite, finding the tetragonal I4/mcm structure transforming to cubic Pm3m with increasing temperature. The transition temperature is 1150 K at 0 GPa, and 2450 K at 140 GPa. The c / a ratio of the tetragonal structure is 1.018 at 100 GPa and increases on compression, as does the static enthalpy difference between tetragonal and cubic structures. The elastic constants of the tetragonal phase at static conditions differ substantially from those of the cubic phase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 59 publications
(47 reference statements)
8
64
3
Order By: Relevance
“…A possible ferroelastic behavior associated with a drastic increase in shear modulus across the tetragonal-cubic phase transition of CaPv was also suggested [Stixrude et al, 1996[Stixrude et al, , 2007. In this study, we investigated the elasticity of cubic CaPv through FPMD computations, and we found a smaller (~50% at 100 GPa) shear modulus of cubic CaPv than was determined by Karki and Crain [1998] (Figure 1b).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A possible ferroelastic behavior associated with a drastic increase in shear modulus across the tetragonal-cubic phase transition of CaPv was also suggested [Stixrude et al, 1996[Stixrude et al, , 2007. In this study, we investigated the elasticity of cubic CaPv through FPMD computations, and we found a smaller (~50% at 100 GPa) shear modulus of cubic CaPv than was determined by Karki and Crain [1998] (Figure 1b).…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, Li et al [2006b] used a tetragonal supercell rather than a cubic primitive cell and found that tetragonal CaPv was stable at LM P-T conditions due to insufficient convergence of the electronic structure with the Brillouin zone sampled only on the Γ point as shown in our previous study [see Kawai and Tsuchiya, 2014]. Then, they reported the elasticity of tetragonal CaPv at high temperatures, which is drastically different from the computation at static conditions by Crain, 1998 andStixrude et al [2007]. Accordingly, no theoretical studies have investigated the elasticity of cubic CaPv at LM P-T conditions.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, the anharmonic part representing a higher order of approximation is negligible; (ii) in general, apart from some particular cases such as Ca-perovskite (Stixrude et al, 2007), anharmonicity loses impact at high-pressure (Stacey and Isaak, 2003;Wentzcovitch et al, 2010).…”
Section: Equlibrium Constantmentioning
confidence: 99%